2023
DOI: 10.3390/ijms24032901
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NF-κB in Endometrial Diseases in Humans and Animals: A Review

Abstract: The expression of genes of various proinflammatory chemokines and cytokines is controlled, among others, by the signaling pathway of the nuclear factor kappaB (NF-κB) superfamily of proteins, providing an impact on immune system functioning. The present review addresses the influence and role of the NF-κB pathway in the development and progression of most vital endometrial diseases in human and animal species. Immune modulation by NF-κB in endometritis, endometrosis, endometriosis, and carcinoma results in cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Other risk factors for endometriosis in adolescence than obstructive Müllerian anomalies is positive family history, early menarche, lean body size, low birth weight, intense physical activity and passive smoking increase, which is not quite similar to endometriosis in adults [ 7 ]. Although retrograde menstruation is the main theory of the development of endometriosis, there are other mechanisms like coelomic metaplasia, implantation through the blood or lymphatic vessels, or differentiation from blood cells, hormonal regulation of inflammatory responses, and failure of the immune system [ 2 , 14 , 15 , 16 ]. Neonatal uterine bleeding (NUB) is one of the explanations for endometriosis developing in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for endometriosis in adolescence than obstructive Müllerian anomalies is positive family history, early menarche, lean body size, low birth weight, intense physical activity and passive smoking increase, which is not quite similar to endometriosis in adults [ 7 ]. Although retrograde menstruation is the main theory of the development of endometriosis, there are other mechanisms like coelomic metaplasia, implantation through the blood or lymphatic vessels, or differentiation from blood cells, hormonal regulation of inflammatory responses, and failure of the immune system [ 2 , 14 , 15 , 16 ]. Neonatal uterine bleeding (NUB) is one of the explanations for endometriosis developing in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that E2 levels in peripheral circulation are inversely correlated with endometritis prevalence (Wu et al, 2018). It has been reported that the uterus is susceptible to infections/inflammation (endometritis) with the decreasing of blood estrogens concentration and is resistant to infections/ inflammation (endometritis) with the increase of blood estrogens concentration (Zdrojkowski et al, 2023). In addition, it has been shown that disruption of estrogen secretion in endometritis (Green et al, 2011;Zralý et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The overproduction of ROS is an important inducer of chronic NF-κB-mediated inflammatory responses [ 20 ] which can trigger cells into pathologies. Under physiological conditions, the NF-κB subunit p65 and progesterone receptor are mutually repressed [ 21 ]. Progesterone inhibits the NF-κB-induced pro-inflammatory factors in endometriotic cells [ 18 , 21 ].…”
Section: Female Reproduction Regulated By Reactive Oxygen and Nitroge...mentioning
confidence: 99%
“…Under physiological conditions, the NF-κB subunit p65 and progesterone receptor are mutually repressed [ 21 ]. Progesterone inhibits the NF-κB-induced pro-inflammatory factors in endometriotic cells [ 18 , 21 ]. High mobility group box-1 (HMGB-1) activates NF-κB via binding to its TLR4 (Toll-like receptor 4) receptor and induces inflammatory responses with sustained OS [ 22 ].…”
Section: Female Reproduction Regulated By Reactive Oxygen and Nitroge...mentioning
confidence: 99%
See 1 more Smart Citation